A Proposed Functional Analysis of Transmission Prevention Behaviors for a Respiratory Virus (SARS-CoV-2). - Shawler, Lesley A.; Blair, Bryan J. (Behavior & Social Issues, 2021)
The coronavirus (SARS-CoV-2) pandemic has had a global impact on lives everywhere and has led to the disruption of, and interference with, virtually every aspect of life. In response, leading experts, political leaders, doctors, and scientists have released guidelines that attempt to prevent and mitigate the exponential rate of infection. The response to these safety recommendations has produced tremendous behavior variability as a society. Although a plethora of factors are likely relevant, a more complete analysis of human behavior during this time might help explain this disparity. The principles of applied behavior analysis allow for a functional analysis of an individual's use of transmission prevention behaviors (TPBs) during the SARS-CoV-2 pandemic. Thus, the purpose of this discussion is to provide a conceptual analysis for some possible explanations for why individuals might or might not engage in virus TPBs, as well as some recommendations to help combat the current pandemic, as well as those in the future.